The Comparisons of Cerebral Hemodynamics Induced by Obstructive Sleep Apnea with Arousal and Periodic Limb Movement with Arousal: A Pilot NIRS Study - Zhang, Zhongxing; Schneider, Maja; Laures, Marco; Qi, Ming; Khatami, Ramin (Frontiers in Neuroscience, 2016)
Obstructive sleep apnea syndrome (OSA) and restless legs syndrome (RLS) with periodic limb movement during sleep (PLMS) are two sleep disorders characterized by repetitive respiratory or movement events associated with cortical arousals. We compared the cerebral hemodynamic changes linked to arousals related to periodic apneas/hypopneas (AHA) in four OSA-patients with arousals related to periodic limb movements (PLMA) in four patients with RLS-PLMS using near-infrared spectroscopy (NIRS). AHA induced homogenous pattern of periodic fluctuations in oxygenated (HbO2) and deoxygenated (HHb) haemoglobin, i.e., the decrease of HbO2 was accompanied by an increase of HHb during the respiratory event and resolved to reverse pattern when cortical arousal started. Blood volume (BV) showed the same pattern as HHb but with relative smaller amplitude in most of the AHA events. These changing patterns were significant as Wilcoxon signed-rank tests gave p<0.001 when comparing the area under the curve of these hemodynamic parameters to zero. By contrast, in PLMA limb movements induced periodic increments in HbO2 and BV (Wilcoxon signed-rank tests, p<0.001), but HHb changed more heterogeneously even during the events coming from the same patient. Heart rate (HR) also showed different patterns between AHA and PLMA. It significantly decreased during the respiratory event (Wilcoxon signed-rank test, p<0.001) and then increased after the occurrence of cortical arousal (Wilcoxon signed-rank test, p<0.001); while in PLMA HR first increased preceding the occurrence of cortical arousal (Wilcoxon signed-rank test, p<0.001) and then decreased. Our results show that both AHA and PLMA induce changes in cerebral hemodynamics. The occurrence of cortical arousal is accompanied by increased HR in both events, but by different BV changes (i.e., decreased/increased BV in AHA/PLMA, respectively). HR changes may partially account for the increased cerebral hemodynamics during PLMA; while in AHA probably vasodilatation within the respiratory event mediated by hypoxia/hypercapnia is more crucial for the post-arousal hemodynamics. The decrement/increment in BV may suggest vasoconstriction/vasodilatation after cortical arousals in AHA and PLMA, respectively. The differences between changes of cerebral hemodynamics and HR may indicate different pathological mechanisms behind these two sleep disorder events.